A content analysis of selected research studies on rural development in Thailand, 1977-1985 - Ploenchan Akevanich; Vallejo, Rosa M.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
This study is the first attempt to compile a bibliography of selected research studies on rural development in Thailand, with complete bibliographic information, descriptors, availability of each title, abstract, and various indices, together with the content analysis of all listed titles. It is intended to serve primarily rural development researchers, administrators, policy-makers, and instructors. It is also intended to enable them to locate the relevant information on rural development of the country, as well as to identify the gaps in the research studies in terms of subject and geographic areas. The bibliography is limited to research studies published during 1977-1985.
This study makes use of documentary research and examination of the resources of 18 libraries/information center/clearinghouse of the Thai government agencies, academic institutions, foreign and international organizations, all located in Bangkok, Thailand.
The 475 research studies listed in the bibliography, cover eight subject categories on rural areas, rural population and rural development in Thailand, namely: policies and planning; agriculture; industrial development; application of science and technology; physical infrastructure, natural resources and environment; human resources development and institutions; health and social services; and general (society, community, village).
The content analysis shows the following results: 1) The most number of research studies were published in 1984, 98 or 20.63 percent while the smallest number were published in 1977, 14 or 2.94 percent. 2) Among 8 different types of materials included in this study (survey, development project, descriptive/documentary research, village study, project evaluation, pilot/feasibility study, masteral thesis/special problem, doctoral dissertation), the biggest number are surveys (153 or 32.21 percent), and the smallest are pilot/feasibility studies (11 or 2.32 percent). 3) Most of the research studies were published in Thai (308 or 64.84 percent), followed by English (152 or 32 percent), and in both languages (15 or 3.16 percent). 4) The Thai scholars produced the most number of research studies during 1977-1985, 285 or 66 percent. 5) The biggest number of the listed research studies are available at the Thailand Information Center (TIC) of Chulalongkorn University (164 or 25.447 percent), which is a depository of research studies in Thailand. 6) The most number of research studies are about agriculture and its relevant areas, 143 or 20.46 percent. 7) Most of the research studies are focused on the Northeastern Region of Thailand, which is the poorest part of the country.
There are, however, certain limitations in undertaking this study, especially sources of the information and subject specialties of the studies which are beyond the writer's knowledge and experience; e.g., medical science, etc. The most important of all, it was found out that to compile a complete bibliography on the field is far beyond one-person's capacity. It is, therefore, recommended that the national-level bibliography on rural development in Thailand be compiled with the NESDB as the coordinating center in collaboration with major concerned ministries and leading academic institutions. The proposed bibliography should include periodical articles, proceedings of conferences, etc., technical reports and others not included in the present bibliography.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Rural development -- Research; Rural development -- Bibliography. -- Thailand